JOURNAL OF «AVICENNA BULLETIN» - 20 YEARS - M. K. GULOV; A. K. BARATOV (Avicenna Tajik State Medical University, 2019)
The article, devoted to the 20th anniversary of the journal "Avicenna Bulletin", reflects the historical background of its creation, tells about the contribution of those scientists who were in the first series of the journal. Information on the main stages of the formation of Avicenna Bulletin is given. In 1999, the journal was registered by the Ministry of Culture of the Republic of Tajikistan (No. 464 of January 5, 1999) and re-registered on 12.11.2018, No. 084/97. Since 2003, the journal has been included in the "List ..." of the Higher Attestation Commission of Russia. Since 2008, Avicenna Bulletin has been presented in the Russian Scientific Citation Index (RSCI). It should be noted that the journal's two-year impact factor increased from 0.02 in 2013 to 0.453 by 2018, i.e. 22 times, and the growth of the five-year impact factor during the same period amounted from 0.024 to 0.320, i.e. 13 times. In 2009, the journal was assigned the International Standard Serial Number (ISSN). During 20 years of its existence on the pages of Avicenna Bulletin were published 1641 articles including 1343 works submitted by Tajik researchers and 298 articles by foreign scientists. In 2017, Avicenna Bulletin joined the Publishers International Linking Association (PILA), and each article is assigned a unique identification number - DOI (Digital Object Identifier). To date, Avicenna's Bulletin adheres to the "Uniform Requirements for Manuscripts Submitted to Biomedical Journals" formulated by the International Committee of Medical Journal Editors (ICMJE), as well as the provisions developed and approved by the Committee on Publication Ethics (COPE). In the year of its anniversary, Avicenna Bulletin will continue the glorious traditions based on the principles of objectivity, transparency, goodwill, demanding, and ethics, and will also intensify efforts to improve its internal and external content.